Pathways to Offense Charging: Examining Defense Decision-Making During Case Processing - Henry, Tri Keah S. (Criminal justice and behavior, 2023)
Prosecutors are afforded significant discretionary power in the current justice system. While much attention has been given to the factors that influence charging decisions, little is known about decision-making in the charging process itself. Moreover, research has yet to examine the mechanisms used to initiate charging: grand jury indictments or the information. As these charging processes are characteristically different and may have significant implications for case processing and justice outcomes, it is important to explore what factors influence decision-making at this early stage. The current study addresses these shortcomings using case-processing data from a large urban jurisdiction. Results indicate significant differences between defendants charged via grand jury and information processes. In addition, charging pathways have important consequences for case outcomes.